Dexmedetomidine modulates neuroinflammation and improves outcome via alpha2-adrenergic receptor signaling after rat spinal cord injury. (December 2019) - Gao, Jiandong; Sun, Zhihua; Xiao, Zhaoyang; Du, Qihang; Niu, Xinhuan; Wang, Gongming; Chang, Yu-Wen; Sun, Yongtao; Sun, Wei; Lin, Amity; Bresnahan, Jacqueline C.; Maze, Mervyn; et al.
Abstract: Background: Spinal cord injury induces inflammatory responses that include the release of cytokines and the recruitment and activation of macrophages and microglia. Neuroinflammation at the lesion site contributes to secondary tissue injury and permanent locomotor dysfunction. Dexmedetomidine (DEX), a highly selective α2-adrenergic receptor agonist, is anti-inflammatory and neuroprotective in both preclinical and clinical trials. We investigated the effect of DEX on the microglial response, and histological and neurological outcomes in a rat model of cervical spinal cord injury. Methods: Anaesthetised rats underwent unilateral (right) C5 spinal cord contusion (75 kdyne) using an impactor device. The locomotor function, injury size, and inflammatory responses were assessed. The effect of DEX was also studied in a microglial cell culture model. Results: DEX significantly improved the ipsilateral upper-limb motor dysfunction (grooming and paw placement; P <0.0001 and P =0.0012), decreased the injury size ( P <0.05), spared white matter ( P <0.05), and reduced the number of activated macrophages ( P <0.05) at the injury site 4 weeks post-SCI. In DEX-treated rats after injury, tissue RNA expression indicated a significant downregulation of pro-inflammatory markers (e.g. interleukin [IL]-1β, tumour necrosis factor-α, interleukin (IL)-6, and CD11b) and an upregulation of anti-inflammatory and pro-resolving M2 responses (e.g. IL-4, arginase-1, and CD206) ( P <0.05). In lipopolysaccharide-stimulated cultured microglia, DEX produced a similar inflammation-modulatory effect as was seen in spinal cord injury. The benefits of DEX on these outcomes were mostly reversed by an α2-adrenergic receptor antagonist. Conclusions: DEX significantly improves neurological outcomes and decreases tissue damage after spinal cord injury, which is associated with modulation of neuroinflammation and is partially mediated via α2-adrenergic receptor signaling.